Analisis Tingkat Pengetahuan Mahasiswa Kedokteran Universitas Tarumanagara Angkatan 2022 terhadap Bantuan Hidup Dasar (BHD) - Myiesha Pravina Rifayanto; Mochamat Helmi (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Basic Life Support (BLS) is a crucial basic skill in the management of medical emergencies, especially in increasing the chances of survival of patients who experience sudden cardiac arrest. BLS actions performed fast and precisely have been proven to significantly increase survival rates. Therefore, this skill is important for all levels of society, especially medical students who will be at the forefront of providing first aid in the health sector. This study aims to measure the level of knowledge about BLS in 231 students of the Faculty of Medicine, Tarumanagara University class of 2022 who have not been exposed to official lecture modules related to BLS. The research design used was descriptive with a cross-sectional approach and simple total sampling technique. The results showed that 58% of respondents had a good level of knowledge, 33.3% were moderate, and 8.7% were lacking. The highest understanding was found in basic aspects such as breathing assessment (99.6%) and awareness that BLS can be performed by anyone (97.4%), reflecting good mastery of basic cognitive concepts. However, understanding of technical aspects such as breath support (44.2%) and pulse assessment (39%) was still low. Therefore, it is very important to improve BLS knowledge and skills through formal training in the curriculum and non-formal such as seminars, workshops, and other educational activities to improve student preparedness in providing first aid, as well as supporting the improvement of the quality of health services in the aspect of emergency.